The voluntary intake and rumen digestion by grazing goats and sheep of a low-quality pasture from a semi-arid land - Alcaide, E M; García, M A; Aguilera, J F (Livestock Production Science, 1997)
An experiment was carried out in late autumn with goats and wethers fitted with permanent ruminal cannulae, grazing in a semi-arid area of South Spain. Shrubs were the most available plant species, although natural vegetation also included trees and grasses. In general, the dominant species of the available vegetation accounted for the highest proportion in the selected diet. Similar proportion and species of grasses were found in the pasture selected by goats and wethers, whereas interspecies differences were observed regarding the selection of shrubs and tree species. Crude protein content was similar in selected diets by goats and sheep, but a higher unavailable N proportion was found for sheep (27.1 and 30.0% of total N for goats and sheep, respectively). Digestibility of forage selected was higher for goats than for wethers. Voluntary intake was significantly (P < 0.05) higher in goats than in sheep; the metabolizable energy intake for goats was higher than their maintenance requirements but failed to meet maintenance needs for wethers. Fermentative rumen activity was moderate and similar for goats and sheep. No interspecies differences were found in rumen fermentation parameters except for molar proportions of acetic and propionic acid and for acetic/propionic ratio, which were significantly higher in wethers. The degradation rate tended to be faster in goats, whereas potential and effective degradability tended to be similar in goats and sheep.
Keywords: Goats; intake; rumen fermentation; semi-arid land; Sheep